Set-theoretical model of a monitoring system for a potentially dangerous object using a multi-purpose fleet of unmanned aerial vehicles - Fesenko, H. V. (Systems and Technologies, 2020)
The current state of development of unmanned aerial vehicles (UAVs) and the miniaturization of special on-board equipment of them make them an effective tool for improving the reliability, survivability and capacity of regular monitoring systems for nuclear power plants (NPP) and other potentially dangerous objects (PDOs). UAVs are able to perform the functions of measuring instruments and deploy multi-channel wireless communication networks between measuring instruments and crisis centers. The aim of the paper is to develop a set-theoretic model of the PDO monitoring system using a multi-purpose fleet of UAVs on theexample of the Zaporizhzhia NPP monitoring system.The general structural scheme of the PDO monitoring system is constructed and the set-theoretical model based on it is developed. Recommendations for model  adjustment in case of deployment of a multi-purpose UAV fleet are formulated. It is noted that for the formation of a multi-purpose fleet of UAVs it is necessary to have information about: measuring instruments, the functions of which can be performed by UAVs; objects of the PDO monitoring system, between which wireless channels are deployed; the number of the channels, wireless technologies used; the length of the wireless network; additional functions to be performed by the multi-purpose fleet (photos, videos, thermal imaging monitoring, etc.); the number of UAV s hifts to ensure uninterrupted operation of the wireless channels formed by them and to perform other tasks of the post-accident monitoring. The process of developing a set-theoretic model and its correction after the deployment of a multi-purposeUAV fleet is shown on the example of the Zaporizhzhia NPP monitoring system. The capabilities of the fleet have been identified, in particular regarding the formation of sixteen wireless networks and the performance of the functions of air stations for radiation and meteorological monitoring. The deployment of a  multipurpose fleet consisting of five groups of UAVs and one airborne radiation control station to perform the functions of measuring instruments and communication channels that failed due to a nuclear accident is shown.